The Influence of Professionalism, Independence, and Competence on Materiality Level Consideration at the Inspectorate General of BPK - Azhar, Muhammad Hakim; Widyasari, Widyasari (Devotion : Journal of Research and Community Service, 2025)
This study aims to analyze the influence of auditor professionalism, independence, and competence on materiality level judgment at the Inspectorate General of the Audit Board of Indonesia (BPK). The background of this research is based on the importance of individual auditor factors in determining materiality levels, which are a crucial aspect of the financial audit process. This research uses a quantitative approach with a survey method through questionnaires distributed to BPK auditors. The data obtained were analyzed using multiple linear regression to examine the relationships between variables. The results of the study indicate that professionalism has a significant effect on materiality level judgment, whereas independence and competence do not have a significant effect. This research is expected to contribute to auditors, users of financial statements, and supervisory institutions in improving audit quality and supporting reliable financial reporting-based decision-making.